Characterization of Newcastle Disease Virus Isolated from Peacocks in Palembang City, South Sumatra - Liza Angeliya; Akbar Agus Anshori Mussama; Syarifah Alawiyah; Tri Guntoro; Eko Agus Srihanto; Yuli Purwandari Kristianingrum; Widya Asmara; Michael Haryadi Wibowo (Jurnal Sain Veteriner, 2023)
Introduction: Newcastle Disease (ND) is an infectious disease in various types of poultry caused by the Newcastle Disease Virus (NDV). Cases of ND in Indonesia have been reported in commercial and backyard chickens, pigeons, ducks and geese, even in eagles and peacocks. Peacock is a wild bird protected by Indonesia's Government Regulation No. 7 of 1999. This study aims to identify, isolate and characterize the NDV molecularly in cases diagnosed as ND in peacocks. Method: Samples were obtained from organs (lungs and spleen) of peacocks which showed neurological symptoms, diarrhoea and then died. Real-time RT-PCR ND was used to identify the cause of death of the peacock. Virus isolation and observation of embryonic changes and death were carried out on embryonic chicken eggs. Sequencing was carried out to characterize the F and HN entire genes of the NDV. The nucleotide sequences were analyzed using MEGA-X software, including amino acid prediction, analysis of genetic variation at the amino acid level, homology and construction of the phylogenic tree. Result: The results of the sample identification were positive for the Newcastle disease virus. Observations of chicken embryos are stunted, have few feathers, are haemorrhagic, and die in less than 60 hours. Virus isolation was obtained with a titer of 26. Molecular analysis showed that the RRQKRF cleavage site pattern in the F gene had homology of 95.8-97.6% and was in the same branching area as the previous ND virus in Indonesia. There were no amino acid mutations at the antigenic site, glycolysis and neutralization epitopes in the HN gene. Conclusion: The virus isolated from the peacock is a velogenic strain of NDV, subgenotype VII.2 and has a close genetic range to the NDV that has been previously reported in commercial and domestic poultry. This result shows that ND is also a threat to protected wild birds.